Salivary proteomic profile of young healthy subjects - Dongiovanni, P.; Meroni, M.; Aiello, Gilda; D’Amato, A.; Cenzato, N.; Casati, S.; Damiani, G.; Fenoglio, C.; Galimberti, D.; Grossi, E.; Prati, D.; Lamorte, G.; et al. (Frontiers in Molecular Biosciences, 2023)
The incidence of noncommunicable diseases (NCDs) has been rapidly ramped up worldwide. Hence, there is an urgent need to non-invasively detect NCDs possibly by exploiting saliva as a 'liquid biopsy' to identify biomarkers of the health status. Since, the absence of standardized procedures of collection/analysis and the lack of normal ranges makes the use of saliva still tricky, our purpose was to outline a salivary proteomic profile which features healthy individuals. Methods: We collected saliva samples from 19 young blood donors as reference population and the proteomic profile was investigated through mass-spectrometry. Results: We identified 1004 proteins of whose 243 proteins were shared by all subjects. By applying a data clustering approach, we found a set of 6 most representative proteins across all subjects including Coronin-1A, F-actin-capping protein subunit alpha, Immunoglobulin J chain, Prosaposin, 78 kDa glucose-regulated protein and Heat shock 70 kDa protein 1A and 1B. Conclusions: All of these proteins are involved in immune system activation, cellular stress responses, proliferation, and invasion thus suggesting their use as biomarkers in patients with NCDs.